Trichome Lengths of the Heterocystous N2-Fixing Cyanobacteria in the Tropical Marginal Seas of the Western North Pacific - Tuo, Sing-how; Mulholland, Margaret R.; Taniuchi, Yukiko; Chen, Houng-Yung; Jane, Wann-Neng; Lin, Yen-Huei; Chen, Yuh-ling Lee (Frontiers in Marine Science, 2021)
Calothrix rhizosoleniae and Richelia intracellularis are heterocystous cyanobacteria found in the tropical oceans. C. rhizosoleniae commonly live epiphytically on diatom genera Chaetoceros (C-C) and Bacteriastrum (B-C) while R. intracellularis live endosymbiotically within Rhizosolenia (R-R), Guinardia (G-R) and Hemiaulus (H-R); although they occasionally live freely (FL-C and FL-R). Both species have much shorter trichomes than the other marine filamentous cyanobacteria such as Trichodesmium spp. and Anabaena gerdii. We investigated the trichome lengths of C. rhizosoleniae and R. intracellularis in the South China Sea (SCS) and the Philippine Sea (PS) between 2006 and 2014. On average, H-R had the shortest trichome lengths (3.5 cells/trichome), followed by B-C and C-C (4.9-5.2 cells/trichome), FL-C (5.9 cells/trichome), and R-R, G-R and FL-R had the longest trichome lengths (7.4-8.3 cells/trichome). Field results showed the trichome lengths of C-C and B-C did not vary seasonally or regionally. However, FL-C and H-R from the SCS and during the cool season had longer trichomes, where/when the ambient nutrient concentrations were higher. R-R, G-R and FL-R also showed regional and seasonal variations in trichome length. Ultrastructural analysis found no gas vesicles within the C. rhizosoleniae cells to assist in buoyancy regulation. Results suggest that the trichome lengths of C. rhizosoleniae and R. intracellularis might be regulated by their diatom hosts’ symbiotic styles and by ambient nutrients. Short trichome length might help C. rhizosoleniae and R. intracellularis to stay in the euphotic zone regardless as to whether they are free-living or symbiotic.